Effect Of Various Renal Biopsy Techniques On Haemato Biochemical Parameters In Dogs (Applied Biological Research, 2012)
Eighteen mongrel dogs of either sex were divided into three equal groups  of six animals each, and were subjected to three different renal biopsy  techniques viz., ultrasound-guided biopsy using 14-G Tru-cut biopsy  needle (Group A), ultrasound-guided fine-needle aspiration biopsy  (Group B) and laparoscope-guided biopsy using laparoscopic biopsy  forceps (Group C) to study the changes in various haemato-biochemical  parameters. The estimations were made just before and at 24, 48 and 72 h  post-biopsy. Haematological parameters (Hb, PCV, TLC and DLC) and  serum protein remained within the normal reference range in all groups  throughout the study period and did not show any significant alterations  at any observation interval within and amongst the groups. In all groups,  serum creatinine and urea nitrogen increased at 24 h post-biopsy, started  to decrease thereafter and by the end of study period the values reached nearer to their corresponding base values. Serum sodium values showed  significant (P
Keywords: Aspiration; biopsy; laparoscope; ultrasound